2015
DOI: 10.1186/s12905-015-0229-7
|View full text |Cite
|
Sign up to set email alerts
|

Rural women are more likely to use long acting contraceptive in Tigray region, Northern Ethiopia: a comparative community-based cross sectional study

Abstract: BackgroundIn the latest report of Ethiopian Demographic and Health Survey (EDHS) 2011, the maternal mortality ratio (MMR) was estimated at 676/100,000 live births, with total fertility rate at 4.8 and contraceptive prevalence rate at 29 %. Knowledge and utilization of long acting contraceptive in the Tigray region are low. This study aims at comparing and identifying factors related to the utilization of long acting contraceptive in urban versus rural settings of Ethiopia.MethodsA comparative community-based c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 7 publications
6
22
1
2
Order By: Relevance
“…Women's lack of adequate knowledge about family planning and fear of side effects played a role in the decision to use contraceptives. This misunderstanding has implications for the uptake and discontinuation of contraception and accords with previous reports from Ethiopia (24,(43)(44)(45)(46). In the present study, a majority of the women were aware of the existence of injectable, pills and implanted contraception.…”
Section: Discussionsupporting
confidence: 89%
“…Women's lack of adequate knowledge about family planning and fear of side effects played a role in the decision to use contraceptives. This misunderstanding has implications for the uptake and discontinuation of contraception and accords with previous reports from Ethiopia (24,(43)(44)(45)(46). In the present study, a majority of the women were aware of the existence of injectable, pills and implanted contraception.…”
Section: Discussionsupporting
confidence: 89%
“…Women's lack of adequate knowledge about family planning and fear of side effects played a role in the decision to use contraceptives. This misunderstanding has implications for the uptake and discontinuation of contraception and accords with previous reports from Ethiopia [24,[42][43][44][45].In the present study, a majority of the women were aware of the existence of injectable, pills and implanted contraception. Although some of the women knew about the intrauterine contraceptive device and condoms, some related condom use with promiscuity rather than a method used in family planning.…”
Section: Discussionsupporting
confidence: 89%
“…Similar results were found in an Ethiopian study where women reported having a negative attitude towards long acting contraceptive methods (LACM) due to allegations of side effects among the community. 31 In this study women who were exposed to positive feedback displayed a favourable attitude towards the Implanon® and were willing to accept the device. This finding is encouraging but contradicts findings in the First World where only 20% of women found that peers influenced their contraceptive choice.…”
Section: Discussionmentioning
confidence: 86%
“…This is in direct contrast with the study done in Ethiopia where they found a significant reduction in LACM use if the partner did not agree with their choice of contraception and two-thirds of the women obtained permission from their partners before using LARC. 31 The participants in our study had full autonomy in their choice of contraception and did not have to ask permission before choosing their method of contraception. At most, the women admitted that it might be a discussion or shared decision-making process.…”
Section: Discussionmentioning
confidence: 99%